PREVALENCE OF SARCOPTIC MANGE IN CAMELS IN PUNJAB, PAKISTAN - M. I. Zahid; A. Maqbool; S. Anjum; K. Ashraf; M. S. Khan; N. Ahmad (Journal of Animal and Plant Sciences, 2015)
Camels are raised in the desert, arid and other rain fed or hard climatic areas of Pakistan, where very little advisory and veterinary services exist due to which they remain exposed to a large number of diseases especially the parasitic infestations of which scabies has the special significance. A cross sectional study was conducted to determine the prevalence of scabies mange infestation in camels in Punjab, a province of Pakistan from September, 2013 to August, 2014. A total of 1489 animals from different camel populations of Punjab were examined for mange mite infestation. 168 animals were found positive for Sarcoptic mange, on the basis of microscopic examination of the skin scrapings. Statistically significant difference (p<0.05) regarding the prevalence of mange mite infestation between different months of the year and seasons prevailing in the country was observed. Furthermore a non-significant difference with reference to the sex and age of animals regarding the prevalence of disease was observed. Negative and significant effect of temperature and non-significant effects of rainfall and humidity were also observed as during the period when there was low temperature the disease increased. “The results of this study revealed that mange infestation is a potential health hazard of the camel population of  Punjab in Pakistan, particularly during the winter season with young and females more prone to the disease, which further requires studies to measure its impact on camel production with economic losses and the ways to control it for the betterment of farmers of the area
Keywords: Camel; Scabies; Arid; Punjab; Sarcoptic mange